Granting Restitution Rights for Victims of Human Trafficking: Legal Protection and Immigration Prevention Efforts in Indonesia - Fajri Dirgantara; Yoyok Ucuk; Subekti Subekti (International Journal of Social Welfare and Family Law, 2026)
Human trafficking constitutes a transnational crime that inflicts physical, psychological, and economic suffering upon its victims. This research aims to analyze the fulfillment of restitution rights for victims of human trafficking and examine preventive efforts from the immigration perspective. According to Law Number 21 of 2007 concerning the Eradication of Human Trafficking, every victim has the right to restitution as compensation for losses suffered. However, implementation in practice still encounters numerous obstacles, including weak law enforcement, limited understanding among law enforcement officers, and insufficient technical regulations. This normative legal research employs statutory and conceptual approaches to examine primary legal materials, including Law Number 21 of 2007, Law Number 6 of 2011 on Immigration, and various implementing regulations. The findings indicate that legal protection for victims of human trafficking has not been optimal, with challenges including difficulties in proving immaterial losses, dual procedural systems between the Human Trafficking Law and Criminal Procedure Code, and weak coordination among law enforcement agencies. The Witness and Victim Protection Agency (LPSK) often cannot guarantee restitution payments as determined by judges. From the immigration perspective, the Directorate General of Immigration plays a strategic role in preventing human trafficking through travel document control, implementation of the Integrated Border Control Management (IBCM) system, education for prospective migrant workers, and cross-sectoral collaboration. However, challenges persist, including complex and evolving modus operandi, limited resources in remote border areas, and inter-agency coordination obstacles. The study concludes that synergy between institutions and improvements in education and regulation are required to ensure victims' restitution rights are fulfilled effectively.